English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6x+5y=6
3x+5y= -12

2007-01-11 08:50:56 · 3 answers · asked by Diamond 1 in Science & Mathematics Mathematics

3 answers

use the subraction method

3x=18

x =6

and substitude 6 to x to get y

3 x + 5Y = -12
18 +5 Y = -12
5Y = - 30
y = -6

2007-01-11 08:55:22 · answer #1 · answered by Anonymous · 1 0

multiple the bottom part with -1.
the 5's cancel out.
so it becomes 3x=18
x=6

and then plug 6 back in to find y.

2007-01-11 08:54:54 · answer #2 · answered by Fabregas 4 · 0 1

solve one equation for one of the variables and then substitute your answer in the other equation.

2007-01-11 09:10:28 · answer #3 · answered by catquarian 2 · 0 0

fedest.com, questions and answers